Program pendampingan latihan fisik dalam upaya peningkatan kesehatan ibu hamil pada masa adaptasi kebiasaan baru - Zulissetiana, Eka Febri; Syifa, Syifa; Nurwany, Raissa; Susilawati, Susilawati (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2022)
Pregnant women as one of the groups vulnerable to COVID-19 infection are advised to stay at home and reduce face-to-face social contact so that they are at risk of reducing physical activity. These lifestyle changes are associated with an increased risk of depression, anxiety, maternal obesity, and various other pregnancy complications such as Gestational Diabetes Mellitus, Preeclampsia, and Low Back Pain. Providing education and assistance as well as empowering pregnant women to do physical exercise regularly is the right strategy to change the pattern of physical activity in order to improve health status during the adaptation period to new habits. This community service activity was carried out to 56 pregnant women in the city of Palembang in the form of providing regular counseling and education. The activity is also accompanied by assistance efforts so that pregnant women can do regular physical exercise for 1 month. The assessment of the success of this community service was carried out by assessing the increase in participants' knowledge before and after the activity, the achievement of the frequency target for all participants during the training session, and also a questionnaire on the benefits of regular physical exercise. The results of the assessment with the questionnaire showed an increase in the average knowledge before and after undergoing the educational program. From this community service activity, it can be concluded that counseling and mentoring activities can be carried out to increase the knowledge and habituation of pregnant women in doing physical exercise, especially during this COVID-19 pandemic.